PROSPECTS OF DEVELOPMENT NANOTECHNOLOGY OF URALS - S.M. Sadovskij (Экономика региона, 2008)
In clause key directions are designated and problems of development nanotechnology are revealed. The estimation of the market nanotechnology Urals is given. Basic elements of system of the state support in regions of the largest projects in sphere nanotechnology and tools of formation of an infrastructure industry are presented.